Back from the rabbit hole. Theoretical considerations and practical guidelines on psychedelic integration for mental health specialists - Greń, Jakub; Tylš, Filip; Lasocik, Michał; Kiraly, Csaba (Frontiers in Psychology, 2023)
The growing interest in and prevalence of the use of psychedelics, as well as the potential benefits and negative consequences associated with psychedelic experiences, create a need for mental health specialists to be able to provide adequate and effective intervention regarding the content and consequences of these experiences, that is, psychedelic integration. At the same time, current graduate training in psychiatry, psychology, psychotherapy, counseling, etc., fails to adequately prepare professionals for such interventions. In order to fill this gap, an international, bottom-up project was established to attempt developing guidelines. This project was conducted by means of literature reviews as well as roundtable discussions among project participants, leading to a consensus on the guidelines’ final scope and content. Drawing from the outcomes of this project, this article presents proposed comprehensive guidelines covering both theoretical and practical aspects of psychedelic integration, that are intended to serve as a resource for various mental health specialists who may encounter individuals in need of support considering their psychedelic experiences. These guidelines encompass clinician-friendly information on the effects of psychedelics, a definition of psychedelic integration, the general theoretical considerations linked to utilization of psychedelic experiences in clinical practice, a simple model organizing the course of psychedelic integration practice, as well as an overview of the current models of psychedelic integration, along with a selective presentation of basic and specific interventions derived from various psychotherapeutic approaches that can be employed in the practice of psychedelic integration.